«Πολιτιστικές διαδρομές, ως μια πολυδιάστατη προοπτική. Η περίπτωση της Ελλάδας.» - (:unkn) unknown (My University, 2021)
Ο σχετικά πρόσφατος θεσμός της πολιτιστικής διαδρομής αποτελεί, εξαιτίας της δυναμικότητάς του, ένα σημαντικό πια «εργαλείο» αξιοποίησης της πολιτιστικής κληρονομιάς. Οι πολιτιστικές διαδρομές είναι αρκετά διαδεδομένες στην Ευρωπαϊκή ήπειρο καθώς προσφέρουν δυνατότητες για αξιοποίηση και προώθηση της πολιτιστικής κληρονομιάς. Η παρούσα διδακτορική διατριβή αποσκοπεί στη μελέτη των πολιτιστικών διαδρομών από διαφορετικές οπτικές γωνίες. Ο σκοπός της παρούσας έρευνας είναι διττός. Πρώτον, η ανάπτυξη ενός μοντέλου για το σχεδιασμό πολιτιστικών διαδρομών στην Ελλάδα, έπειτα από ενδελεχή μελέτη της εγχώριας και της διεθνούς βιβλιογραφίας, καθώς και ο σχεδιασμός πολιτιστικών διαδρομών σε Σπάρτη και Ιωάννινα, σύμφωνα με το μοντέλο που αναπτύχθηκε στο πλαίσιο της παρούσας έρευνας. Δεύτερον, η παρούσα διατριβή αποσκοπεί στο να αποτελέσει ένα εγχειρίδιο αναφορικά με τις πολιτιστικές διαδρομές. Στο πλαίσιο της παρούσας διατριβής πραγματοποιήθηκε έρευνα με τη χρήση ερωτηματολογίου, η οποία στοχεύει στην σκιαγράφηση της εξοικείωσης των πολιτών με τον όρο πολιτιστική διαδρομή, τον βαθμό πληροφόρησης τους αναφορικά με τις πολιτιστικές διαδρομές στην Ελλάδα και επιπλέον, την πρόθεση συμμετοχής των πολιτών στη διαδικασία διαμόρφωσης και επίσκεψης μιας πολιτιστικής διαδρομής. Για την επεξεργασία των δεδομένων της ποσοτικής έρευνας χρησιμοποιήθηκε το στατιστικό εργαλείο SPSS.

Cultural tourism is a fast-growing industry, which attracts the interest of both local and global economic and social players. One aspect of cultural tourism is that of offering cultural routes to visitors in order to enable them better explore the cultural heritage of a region and most importantly to experience a complete cultural visit to a place of interest. Given its potential, the cultural route is an important “tool” for the management and development of cultural heritage. It is an exclusive tourism product, a new approach to the concept of preserving and highlighting cultural heritage. Currently, a constant development concerning the cultural routes is observed in an international level, as it is widely accepted that cultural tourism plays an important role in the world touristic industry. It is this industry that can support, through correct and effective management, local and national economy and reinforce socio-cultural development of the society. The purpose of this research is twofold. Firstly, the development of a model for the design of cultural routes in Greece, following a thorough study of bibliography, as well as the design of cultural routes in Sparta and Ioannina, in accordance with the model developed in the context of this research. Secondly, this research aims to provide a handbook on cultural routes. In the context of this research, a survey was carried out using a questionnaire, which aims to outline citizens familiarity with the term cultural route, their degree of information about cultural routes in Greece and, in addition, the intention to involve citizens in the process of shaping and visiting a cultural route. The statistical tool SPSS was used to process quantitative survey data.
«The Development of Cultural Routes. The Case of Greece.»
Keywords: πολιτιστικός τουρισμός, πολιτιστικές διαδρομές, πολιτιστικές διαδρομές του Συμβουλίου της Ευρώπης, Ελλάδα, έρευνα, Σπάρτη, Ιωάννινα; cultural tourism, cultural routes, Cultural Routes of the Council of Europe programme, Greece, research, Sparta, Ioannina